2021
DOI: 10.1073/pnas.2015482118
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic transmission modeling of COVID-19 on the Diamond Princess cruise ship demonstrates the importance of aerosol transmission

Abstract: Several lines of existing evidence support the possibility of airborne transmission of coronavirus disease 2019 (COVID-19). However, quantitative information on the relative importance of transmission pathways of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains limited. To evaluate the relative importance of multiple transmission routes for SARS-CoV-2, we developed a modeling framework and leveraged detailed information available from the Diamond Princess cruise ship outbreak that occurred … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(127 citation statements)
references
References 49 publications
3
123
0
1
Order By: Relevance
“…Since the app did not collect the data regarding the other behaviors, we were not able to adjust for them. However, there is growing evidence that COVID-19 may spread through aerosols [42][43][44] . Since hand washing does not effectively prevent aerosol transmission while the face mask use does 45 , it is less likely that our findings were confounded by hand washing.…”
Section: Discussionmentioning
confidence: 99%
“…Since the app did not collect the data regarding the other behaviors, we were not able to adjust for them. However, there is growing evidence that COVID-19 may spread through aerosols [42][43][44] . Since hand washing does not effectively prevent aerosol transmission while the face mask use does 45 , it is less likely that our findings were confounded by hand washing.…”
Section: Discussionmentioning
confidence: 99%
“…After investigating the potential contributions of respiratory droplets, aerosols, and fomites among new cases of COVID-19 aboard the Diamond Princess cruise ship, Azimi et al concluded that short-range aerosols were the dominant mode of transmission [15] . Investigating the same outbreak, Xu et al did not find a substantial increase in cases after the stay-in-room policy was implemented, leading them to conclude that the virus was not spread through the central air-conditioning to individual rooms, and that long-range aerosol transmission may not be possible [16].…”
Section: Respiratory Transmission: Respiratory Droplets and Aerosolsmentioning
confidence: 99%
“…The importance of both shorter range and longer range routes of exposure for community transmission has been borne out in studies of outbreaks, in particular the Diamond Princess cruise ship (Azimi et al., 2020) and the Skagit WA choir cluster (Miller et al., 2020). Modeling studies also indicate that both routes are important in the health care setting (Jones, 2020).…”
Section: Introductionmentioning
confidence: 99%